(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2024)
Teenage pregnancy remains a persistent global crisis that profoundly affects the socio-economic wellbeing of nations, citizens and families. The purpose of this study was to assess the relationship between principals’ involvement of parents in students discipline and teenage pregnancy in public secondary schools in Kenya. The article is an extract of a study done in public secondary schools in Machakos County, Kenya. The study was guided by the social learning theory postulated by Albert Bandura. The research utilized a descriptive research design. The research target population comprised of 360 principals, 360 Heads of Department (HoDs) Guidance and Counseling (G&C), 360 Parent Association (PA) chairpersons and, 103,517 students. The study sample size was 450 comprising of 189 principals, 189 HoDs G&C, 36 PA chairpersons and 36 FGD. Questionnaires were used to collect data from the principal’s and HoDs G&C. Interview schedules collected data from the PA chairperson while Focused Group Discussions (FGD) collected data from form three students. Data was analyzed using SPSS software version 25.The correlational analysis findings from the principal and HoDs G&C responses showed a positive and significant relationship between principal’s engagement of parents in student’s discipline and teenage pregnancy (rp =.379 & rh = 0.564; p≤ .01). The study concludes that involving parents enhances learner discipline and can help curb cases of teenage pregnancies. The study recommended that PAs should work collaboratively with principals to make sure that parents are engaged in all matters affecting their children.